Divine benevolence, embodiment and salvation in the teachings of Joseph Smith and the Book of Mormon - Moulton, Tyler Rex (1997)
No abstract. From introduction: "On the whole, this thesis is more concerned with reexamining some fundamental questions than with finding all of the answers. What responses are given are to be viewed as suggestions and possibilities, and certainly not as definitive conclusions"